Diagnostic accuracy of 99mTc-antigranulocyte SPECT/CT in patients with osteomyelitis and orthopaedic device-related infections: A retrospective analysis. (February 2020) - Plate, A.; Weichselbaumer, V.; Schüpbach, R.; Fucentese, S.F.; Berli, M.; Hüllner, M.; Achermann, Y.
Highlights: 99m Tc-antigranulocyte SPECT/CT has a high diagnostic accuracy (88.5%). It may help if standard diagnostics are not applicable or inconclusive. 99m Tc-antigranulocyte SPECT/CT is now recommended by current guidelines. Abstract: Objectives: Conventional imaging techniques are routinely used in the diagnostic work-up of patients with suspected osteomyelitis or orthopaedic implant-associated infections. Hybrid nuclear medicine imaging techniques are a suitable alternative to routine imaging modalities as they provide anatomical and functional information within one procedure. Our study investigated the performance of anti-granulocyte SPECT/CT using 99m Tc-labelled monoclonal antibodies in the diagnosis of osteomyelitis and orthopaedic implant-associated infections. Methods: In this retrospective analysis, we included patients with 99m Tc-antigranulocyte SPECT/CT acquired in the context of a suspected bone and joint infection. All patients underwent routine diagnostics and/or had a clinical follow-up of at least 12 months. Results: 26 episodes were included. Fifteen exams were performed for suspected osteomyelitis, and 11 for suspected orthopaedic implant-associated infection. SPECT/CT was ordered most often if standard diagnostic tests or conventional imaging modalities remained inconclusive. The overall sensitivity and specificity for the diagnosis of an infection were 77.8% and 94.1%, respectively. The positive predictive value was 87.5% and the negative predictive value 88.9%. Diagnostic accuracy was 88.5%. Conclusions: 99m Tc-antigranulocyte SPECT/CT imaging has a high accuracy in the diagnosis of osteomyelitis and orthopaedic implant-associated infections and is a suitable non-invasive diagnostic tool if standard diagnostic examinations are inconclusive or not applicable.